Pengaruh Kepercayaan Konsumen dan Kualitas Produk terhadap Keputusan Pembelian Batu Batako di Kelurahan Wairotang - Felixsia Antonia Irmawati; Antonius Phillipus K.Gheta; Margaretha Yulianti (Universitas Nusa Nipa Maumere, 2026)
The concrete block business is one of the micro-enterprises that develops in Wairotang Village and plays an important role in fulfilling the community’s need for building materials. However, in its development, sales fluctuate from year to year, which is assumed to be influenced by the level of consumer trust and the quality of the products produced. In addition, several problems still occur, such as concrete blocks that crack easily, inconsistent sizes, and varying levels of strength, leading consumers to hesitate in making repeat purchases. This study aimed to determine the influence of consumer trust and product quality on purchasing decisions of concrete blocks in Wairotang Village. The independent variables in this study were consumer trust and product quality, while the dependent variable was purchasing decision. This study was motivated by fluctuations in concrete block sales and the persistence of consumer doubts regarding product quality, including easily cracked blocks, inconsistent sizes, and varying strength levels. These conditions resulted in suboptimal consumer trust, which in turn affected purchasing decisions. This study used a quantitative research method. The population consisted of consumers of concrete blocks in Wairotang Village, and the sampling technique was purposive sampling. Data collection was conducted through questionnaires, observations, interviews, and documentation. The data were analyzed using descriptive analysis, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R^2). The results were expected to show that consumer trust and product quality have a positive and significant influence on purchasing decisions of concrete blocks in Wairotang Village, both partially and simultaneously. A higher level of consumer trust and better product quality lead to increased purchasing decisions. Therefore, concrete block business actors will need to maintain product quality and build good relationships with consumers in order to improve purchasing decisions and ensure business sustainability.